RETRACTED : The Influence of Work Environment, Individual Characteristics, Communication and Work Discipline on Employee Performance at PT. Bank Negara Indonesia (Persero) Tbk. Jakarta City Area - Rosmalita Andarwati; Herry Krisnandi; Kumba Digdowiseiso (Syntax Corporation Indonesia, 2024)
The purpose of this study was to determine the effect of work environment, individual characteristics, communication and work discipline on employee performance in PT. Bank Negara Indonesia (Persero) Tbk. Jakarta City Region. With a sample of 120 employees/respondents. Seals are obtained using the Probability Sampling technique, that is, the required information obtained from all elements has the opportunity to be selected as a sample. Hypothesis testing uses multiple linear regression analysis using SPSS version 24.0. The results showed that work environment, individual characteristics, communication and work discipline on employee performance.